2006
DOI: 10.1186/gb-2006-7-6-r46
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in operons of Streptomyces coelicolor

Abstract: Gene expression in operons

Analysis of the relative transcript levels of intra-operonic genes in Streptomyces coelicolor suggests significant levels of internal regulation.

Abstract Background: Recent studies have shown that microarray-derived gene-expression data are useful for operon prediction. However, it is apparent that genes within an operon do not conform to the simple notion that they have equal levels of expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…This was achieved by combining two RNA sequencing approaches, one that identifies and ‘differentiates’ sites of transcription initiation and endonucleolytic cleavage (dRNA-seq) and another that provides a ‘global’ view of transcript abundance and the boundaries of transcription (gRNA-seq) (Lin et al ., 2013 ). We also conducted a parallel analysis of Escherichia coli , which has been used as a reference for studying Streptomyces gene regulation (Taguchi et al ., 1990 ; Messer and Zakrzewska-Czerwinska, 2002 ; Bralley et al ., 2006 ; Laing et al ., 2006 ; Gatewood and Jones, 2010 ), as well as being an important model, most recently in the development of systems-level understanding (Schwille and Diez, 2009 ; De Smet and Marchal, 2010 ; Hyduke and Palsson, 2010 ; Zhang et al ., 2010 ; Porter et al ., 2011 ). The inclusion of E. coli provided insight over and above that obtained by many groups via extensive study using traditional gene-specific methods such as northern blotting and primer extension (Kime et al ., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by combining two RNA sequencing approaches, one that identifies and ‘differentiates’ sites of transcription initiation and endonucleolytic cleavage (dRNA-seq) and another that provides a ‘global’ view of transcript abundance and the boundaries of transcription (gRNA-seq) (Lin et al ., 2013 ). We also conducted a parallel analysis of Escherichia coli , which has been used as a reference for studying Streptomyces gene regulation (Taguchi et al ., 1990 ; Messer and Zakrzewska-Czerwinska, 2002 ; Bralley et al ., 2006 ; Laing et al ., 2006 ; Gatewood and Jones, 2010 ), as well as being an important model, most recently in the development of systems-level understanding (Schwille and Diez, 2009 ; De Smet and Marchal, 2010 ; Hyduke and Palsson, 2010 ; Zhang et al ., 2010 ; Porter et al ., 2011 ). The inclusion of E. coli provided insight over and above that obtained by many groups via extensive study using traditional gene-specific methods such as northern blotting and primer extension (Kime et al ., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between IGA and various computationally derived characteristics of gene promoters, including binding site counts, quality, and locations were determined by correlation and regression analysis. For each operon, only the IGA of the first gene was included in the statistical analysis, since unequal levels of expression among genes of the same operon are common, likely because of putative internal promoters or because of alternative regulatory mechanisms controlling gene expression within operons 48. In the following sections we give a brief description of the experimental studies used to characterize CRP/ArcA IGA.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been demonstrated that genes within an operon do not conform to the simple notion that they have equal levels of expression (43). Several studies revealed the existence of the internal promoters and read-through terminators in bacterial operons (43,44). These additional promoters are often located downstream of the first gene so that only part of the operon is transcribed from the internal promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory mechanism controlling the transcription of the AcrAB-OprM genes after clarithromycin treatment is indistinct at this point and needs further investigation. However, it has been demonstrated that genes within an operon do not conform to the simple notion that they have equal levels of expression (43). Several studies revealed the existence of the internal promoters and read-through terminators in bacterial operons (43,44).…”
Section: Discussionmentioning
confidence: 99%